Pengenalan Instrumen dan Peningkatan Literasi Keuangan Ibu Rumah Tangga di Lingkungan PCA Kraton Yogyakarta - Romi Bhakti Hartarto; Ibnu Hajar; Danes Quirira Octavio; Sintia Handayani; Faizmal Sugiarto; R. Fadhil Muhammad Ginanjar (Indonesian Journal Publisher, 2024)
The housewife has an important role in the family's financial management. They are responsible for regulating spending, saving, and investing to meet the needs of the family. This community empowerment program aims to introduce investment in financial instruments to the members of PCA Kraton so that they can make smart investment choices and avoid the risk of fake investments. The materials being delivered include financial records using SIAPIK application and stock investments using the Magic application. The findings from a one-way t-test for a paired sample of 25 participants showed an increase in the financial literacy score of the PCA Kraton households by 1.80 points with a 5% significance rate. This indicates that community-serving activities were successful in improving the participants' knowledge of family financial planning and investment instruments